(untitled) (Indian Journal of Veterinary Pathology, 2024)
Ovine pulmonary adenocarcinoma (OPA) is caused by the beta retrovirus i.e. JSRV of Retroviridae family, and reported commonly in sheep and rarely in goats. This study was designed with objectives to detect the JSRV in different biological samples and to characterize it. A total of 656 biological samples (289 lung tissues, 233 blood and 134 nasal swabs) were collected from different slaughterhouses, farms and post mortem facilities located at the northern states of India. Hemi-nested PCR was performed to detect JSRV nucleic acid, which revealed JSRV positivity in 3.79% and 3.06% of sheep and goat samples, respectively. Lung tissues showed highest JSRV positivity i.e. 4.84%, followed by blood samples (3%) and nasal swabs (1.49%). JSRV genome from two lungs tissue samples were amplified by self designed overlapping primers and sequenced. Phylogenetic analysis of both the sequences showed close homology with the exogenous JSRV circulating in the USA and China. Histopathological evaluation of sheep lungs tissues showed OPA lesions (both classical and atypical OPA) in 3.19% of samples. Immunostaining revealed JSRV antigen localization in the proliferating pneumocytes, bronchiolar epithelium and macrophages. Further, immune cells infiltration around the OPA lesions was analyzed by IHC and it was observed that B cells were most predominant. Expression of IFN-γ, TNFα, IL-2, IL-4, IL-6 and IL-10 in most of the JSRV positive lung tissue samples showed the down regulation of these cytokines indicating altered immune response due to OPA, which may increase the susceptibility of the affected animals to other infections.